Penerapan Metode Pembelajaran Kooperatif Tipe Stad Dan Kreativitas Terhadap Peningkatan Hasil Belajar Mata Pelajaran Akuntansi Komputer Siswa Akuntansi Kelas XI SMK Negeri 2 Rambah Tahun 2019/2020 - Armawanti Armawanti (JURNAL PENDIDIKAN ROKANIA, 2022)
The purpose of this study was to explain the process of increasing the activity and learning outcomes of students' biology on the material system of motion in class XI Social Sciences at SMA Negeri 3 Rambah, Rokan Hulu Regency with Problem Based Learning. This type of research is classroom action research (CAR). The subjects of this study were students of class XI IPS SMA Negeri 3 Rambah. This research consists of two cycles, each cycle consists of planning, implementation, observation and reflection. The research instrument was in the form of student activity observation sheets, and learning outcomes test sheets. The data were analyzed with descriptive statistics to see the increase in student activity and learning outcomes. The results showed that problem-based learning can increase student activities which include paying attention to the explanation of the material presented by the teacher, collaborative activities in groups, making presentations, asking and answering questions. pay attention to the explanation of the material presented by the teacher, cooperative activities in groups, and presentation activities. Meanwhile, student learning completeness in the first cycle was 70, in the second cycle it increased to 80%. The conclusion of this research is problem-based learning can increase the activity and learning outcomes of machine biology on the motion system material in class XI Social Sciences SMA Negeri 3 Rambah